Anterior abdominal wall endometrioma: a diagnostic dilemma - Yelurkar, Nilofar Imamhusen; Satia, Meena Naresh; Deekshit, Ananya Rajendra; Badhwar, Vijaya Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The presence of functioning endometrium outside the uterine cavity is often encountered in gynaecological practice but an extremely rare entity is its extra pelvic variant is seen sometimes around the umbilicus, anterior rectus sheath vesical region, also rarely seen around the kidney’s nasal mucosa, lungs and the pleura. The incidence of this condition is as low as 0.03% to 0.15%. Endometrioma of the anterior rectus sheath is well documented in literature but because of its rarity may pose a diagnostic dilemma. Reporting herewith a case of anterior rectus sheath endometrioma where medical line of treatment failed and surgical excision was required.